Becoming to Belong: On the Relation between Infinite Consciousness and the Absolute. Issue 1 (2nd January 2016) - McManus, Matthew
Abstract: My essay focuses on the relation between consciousness and reality. I argue, following Georg Cantor, that consciousness is a potential infinite driven by care to invest itself in the world historically. As human beings develop an authentic sense of self they are driven by good faith to postulate an Absolute infinite, which, following Spinoza, we may call God. Thus God, as the Absolute infinite, constitutes our reality, which I characterize as implicate information explicating itself through time. To live authentically is to recognize the nature of God and commit to Him through faith. Faith means to understand one's self as a potentially infinite consciousness attempting to authentically participate in, and understand, the Absolute of God.